Geometry map algorithms for interactive deformation and real-time visualization - Liu, Qiang (2008)
Laparoscopic surgery is a popular technique that requires intensive training and practice before actual surgery. Computer simulation provides a virtual training environment for surgeons to practise. Surgery simulators are becoming practical with new frameworks that include core components such as enhanced medical imaging, rapid medical data modeling, realistic visualization procedures, and high fidelity animation techniques. The emphasis on cinematic quality rendering has gained importance with the widespread availability of affordable high end graphics capabilities on desktop computers. However, the challenge is the computation of man-machine interaction with the deformable tissues/organs.